Strategi Komunikasi Pendidik Dalam Meningkatkan Budaya Literasi di SMP Kemala Bhayangkari 1 Medan - Br Ginting, Alemina Natasya; Purba, Christin Agustina; Lutfiah, Lutfiah; Pinem , Veronika Mareta (Jayapangus Press, 2025)
The low level of literacy culture among junior high school students, particularly in the Medan area, remains a serious issue that requires immediate attention. This study aims to describe the communication strategies used by teachers in fostering a literacy culture at SMP Kemala Bhayangkari 1 Medan. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The informants in this study consisted of two Indonesian language teachers and one English language teacher. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the teachers implemented four communication strategies: personal, participatory, collaborative, and reflective. The implementation of the 15-Minute Literacy and Literacy Wednesday programs successfully established consistent reading habits among students. The communication channels used included direct interaction, WhatsApp groups, social media, and digital media such as videos and e-books. Teachers acted as facilitators and motivators in building two-way communication involving both students and parents. Therefore, adaptive multi-channel communication strategies can be replicated in other schools to strengthen students’ literacy culture, offering both theoretical and practical contributions.